Analysis of gaze characteristics with eye tracking system during repeated breath holding exercises in underwater hockey elite athletes [Elit Sualti Hokeyi Sporcularinda Tekrarlanan Nefes Tutma Egzersizleri Esnasinda Göz Takip Sistemi Ile Bakis Karakteristikleri Analizi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
Nowadays eye-tracking technologies become an inherent part of scientific researches. By the use of eye-tracking systems scientists can detect eye movements and analyze human cognitive processing of visual information for interactive and diagnostic applications. The research of eye-tracking in sports concentrates on the performance of the athletes and how it is related to perceptual function. The purpose of these kind of studies is to plan the exercises in order to improve the performance of the athletes by training their vision and eye-tracking behaviour. In this study, it is planned to show the difference of the control group and elite underwater hockey athletes by analysing their eye-tracking systems and vision behaviour during breath holding exercises. A series of Images collected during shooting at the underwater hockey competetions were presented to the subjects. 30 photographs were shown to the elite athletes and the control group who were athletes in their past career in various sport branches but not active,anymore. Each photograph were shown in 2 seconds in the screen during holding their breath for 60 seconds. The paradigm is repeated in 4 set and it is expected to explore their previously-notified teammate with eyes-open and focused on different match images. By tracking the eye movements, the number of average eye fixation has been calculated. Although no differences have been observed in the first 3 phases, a significant distinction has been observed in phase 4. Thus, it provides advantage to the athlete group to reach the correct number by resisting the effects of breath holding arising from the branch at phase 4. Up to our knowledge this study is one of the promising studies. © 2016 IEEE.
Keywords: Breath hold; Eye tracking; Underwater hockey